An antibacterial ABS composite material and preparation method thereof
By modifying silver aluminosilicate, silver ions are loaded into the pore structure, combined with hydrothermal method and twin-screw extrusion technology, antibacterial ABS composite material is prepared, which solves the problem of silver ions being easily discolored and has a short antibacterial validity period, and achieves the Long-term antibacterial effect and excellent mechanical properties.
Patent Information
- Application Number
- CN202210978001.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-08-16
AI Technical Summary
In the preparation of existing ABS antibacterial plastics, silver ions are prone to discoloration and have a short antibacterial validity period. Titanium dioxide requires ultraviolet light and oxygen to play a bactericidal effect. The safety and heat resistance of nano silver oxide are poor, resulting in poor antibacterial effect.
Modified silver-loaded aluminosilicate is used to load silver ions into the pore structure, and porous aluminosilicate is prepared by hydrothermal method to form a high specific surface area and a network-shaped microporous structure, fix and sustainably release silver ions, and combine Processing aids such as dispersants and antioxidants are granulated by twin-screw extruder to prepare antibacterial ABS composites.
It has achieved the solution to the problem of silver ion discoloration, extended the effective time of antibacterial, improved the antibacterial effect and mechanical properties, simple operation, high loading rate, and good material dispersion.
Smart Images

Figure BDA0003799169260000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial composite materials and relates to an antibacterial ABS composite material and a preparation method thereof. Background Art
[0002] Acrylonitrile-styrene-butadiene copolymer (ABS) is an engineering plastic with excellent comprehensive performance. This type of plastic is easy to process, shiny, and has good mechanical properties. It is currently widely used in electronic appliances and daily life. With the improvement of living conditions, people have higher and higher requirements for the daily use of ABS plastics, especially in medical and health care, home appliances and daily necessities. ABS products are not only required to have good mechanical properties, thermal properties, etc., but also have excellent antibacterial properties.
[0003] Take the home appliance industry as an example. Home appliances are the most in contact with people in daily life, and the more harmful microorganisms grow on home appliances, the more harmful they are to humans. The interior of the air conditioner is relatively humid and easy to breed microorganisms, which are harmful to the human body. They will enter the room through the air conditioner's circulation system and cause air conditioning disease. Therefore, people replace the plastic parts inside the air conditioner with antibacterial products to solve the problem of air conditioning disease.
[0004] At present, in the preparation of ABS antibacterial plastics, silver and titanium dioxide are often used for modification to achieve the antibacterial effect. However, silver ions have a strong photosensitivity reaction and are very easy to change color when exposed to light or stored for a long time. When in contact with water, silver ions are easy to precipitate, resulting in a short antibacterial effective period. Photocatalytic antibacterial agents represented by titanium dioxide are characterized by high heat resistance, but they must be exposed to ultraviolet light and have the presence of oxygen or water to have a bactericidal effect.
[0005] In the "Preparation and Performance Study of Silver-Based Antibacterial ABS Plastics", a simple silver-based material was added to ABS to obtain a good antibacterial effect. However, silver ions have a strong photosensitivity reaction and are very easy to change color when exposed to light or stored for a long time. Silver ions are easily precipitated when in contact with water, resulting in a short antibacterial effectiveness period.
[0006] The Chinese patent application document (publication number: CN113072780A) uses antibacterial masterbatch to prepare antibacterial ABS materials. It mainly uses lignin and loaded precious metals to achieve antibacterial effects. However, antibacterial agents represented by lignin are not heat-resistant, and the output is limited by the production scale and process conditions of the enterprise, and the efficacy is generally short.
[0007] The Chinese patent application document (CN104987648A) mainly uses chitosan and sorbitol to achieve a synergistic antibacterial effect. However, it is prone to problems such as poor heat resistance, easy dissociation, and poor compatibility, and has not yet met the conditions for large-scale use.
[0008] The Chinese patent application document (CN105670202A) uses three antibacterial agents, nano titanium dioxide, nano silver oxide, and polyhexamethylene guanidine phosphate, which are added to ABS at the same time. However, titanium dioxide must be exposed to ultraviolet light and have the presence of oxygen or water to have a bactericidal effect; polyhexamethylene guanidine phosphate has the disadvantages of toxicity, poor safety, heat resistance, poor chemical stability, easy hydrolysis, easy to make microorganisms resistant, and short service life. Summary of the invention
[0009] The purpose of the present invention is to solve the above problems in the prior art and to provide an antibacterial ABS composite material with good particle dispersion effect and antibacterial effect, long effective time and excellent mechanical properties.
[0010] The purpose of the present invention can be achieved through the following technical scheme: an antibacterial ABS composite material, the composite material comprises the following raw materials in parts by weight: 90-110 parts of ABS recycled material, 0.5-3 parts of modified silver-loaded aluminosilicate, and 1.5-4 parts of processing aids.
[0011] Metal ions have a bactericidal function, but silver ions have the best effect. When silver ions come into contact with the cell wall of microorganisms or enter the interior of cells, they can destroy the protein structure of microorganisms, causing the death of microorganisms or metabolic functional disorders. When trace metal ions in the liquid medium come into contact with the cell membrane of microorganisms, since the cell membrane is negatively charged, Coulomb force attraction will be generated between the metal ions, so that the two are firmly combined. After the metal ions enter the cells, they will interfere with DNA synthesis and cause the death of microorganisms. However, the direct addition of silver will easily change color due to exposure to light or long-term storage, affecting the color of the product. In addition, the release rate of silver ions is very fast, which affects the long-term antibacterial effect of the product. The present invention uses a loading method to carry silver ions into a carrier material with a pore structure, which can effectively solve the problem of silver ion discoloration, while also improving the dispersibility of silver in the matrix material and controlling the release rate of silver ions. The modified silver-loaded aluminosilicate of the present invention expands the scope of application in actual scenarios.
[0012] In the above-mentioned antibacterial ABS composite material, the modified silver-loaded aluminosilicate comprises the following raw materials in parts by weight: 2-4 parts of tetraethyl orthosilicate, 39-48 parts of anhydrous ethanol, 0.5-2.0 parts of porous aluminosilicate, 0.5-2 parts of silver nitrate, and 40-70 parts of ethylene glycol.
[0013] In the above-mentioned antibacterial ABS composite material, the size of the porous aluminosilicate is 50-150 nm, wherein the aluminum-silicon ratio is 1:(15-25).
[0014] Preferably, the specific preparation method of porous aluminosilicate comprises the following steps: uniformly mixing nano oxide and microporous alumina at 180-220 rpm to obtain a mixture, adding a titanate coupling agent and mixing at a high speed at 480-520 rpm for 5-8 min, ultrasonicating at room temperature for 25-35 min and then standing, then using a hydrothermal method to control the hydrothermal temperature to 140-160° C. for 8-12 h, and finally adjusting the pH to 3-5 to obtain porous aluminosilicate.
[0015] Preferably, the mass ratio of nano-oxide to microporous alumina is (4-6):1.
[0016] Preferably, the nano-oxide is nano-zinc oxide, nano-silicon oxide, or nano-titanium oxide with a particle size of 20-30 nm.
[0017] Preferably, the titanate coupling agent is added in an amount of 0.5-2% by mass of the mixture.
[0018] Preferably, the ultrasonic conditions are 55-65 Hz, 950-1100 W.
[0019] In the aluminosilicate of the present invention, both aluminum oxide and silicon oxide are tetrahedral structures. The connection mode of silicon-oxygen tetrahedron is complex anion configuration, and the cavities of this configuration can accommodate silver ions to protect the silver ions from light reaction.
[0020] In the above-mentioned antibacterial ABS composite material, the processing aid includes at least one of a dispersant, a lubricant, and an antioxidant.
[0021] Preferably, the dispersant is a polyethylene wax dispersant.
[0022] Preferably, the lubricant is a stearic acid lubricant.
[0023] Preferably, the antioxidant is antioxidant 225.
[0024] In the above-mentioned antibacterial ABS composite material, the preparation method of the modified silver-loaded aluminosilicate comprises the following steps:
[0025] S1, adding ethyl orthosilicate to anhydrous ethanol, and then adding porous aluminosilicate to carry out heating reaction to obtain modified aluminosilicate;
[0026] S2. In a light-proof environment, dissolve silver nitrate in ethylene glycol and stir, then add modified aluminosilicate and heat, and finally wash and dry to obtain modified silver-loaded aluminosilicate.
[0027] Preferably, the modified silver-loaded aluminosilicate is in a ribbon-like stacking morphology with a size of 50-150 nm.
[0028] The modified silver-loaded aluminosilicate prepared by the hydrothermal method of the present invention can realize controllability and modifiability at the molecular level, and the prepared material has the characteristics of uniform particles, good dispersibility, high purity, high crystallinity, less agglomeration, etc. During the modification, ethyl orthosilicate is added as a surface modifier, and combined with the effect of silver ions, a modified aluminosilicate porous material with regular morphology, uniform particles, uniform particle size, and a banded needle structure is synthesized. The modified silver-loaded aluminosilicate prepared by the present invention has an extremely high specific surface area and a connected network-like microporous structure, and the pore structure can be modified to varying degrees within a range as required.
[0029] The stronger the reaction activity, the larger the size of the silver particles formed. The present invention uses ethylene glycol and its added amount to ensure that the reduction reaction proceeds while controlling the reaction rate to ensure that the size remains consistent and is at the nanometer level.
[0030] In the above-mentioned antibacterial ABS composite material, the heating reaction temperature in step S1 is 135-145° C. and the reaction time is 24-48 hours.
[0031] In the above-mentioned antibacterial ABS composite material, the heating temperature in step S2 is 85-95° C. and the heating time is 48-72 hours.
[0032] In the above-mentioned antibacterial ABS composite material, the drying in step S2 is vacuum drying at a temperature of 80-100° C. for a period of 1-3 days.
[0033] The present invention also provides a method for preparing the antibacterial ABS composite material, which comprises the following steps: uniformly mixing ABS recycled material with modified silver-loaded aluminosilicate and processing aid, and finally extruding and granulating in a twin-screw extruder.
[0034] In the above-mentioned method for preparing an antibacterial ABS composite material, the temperature of the first zone of the twin-screw extruder is 180-100°C, the second zone is 180-200°C, the third zone is 210-230°C, the fourth zone is 205-225°C, the fifth zone is 200-220°C, the residence time is 1-2min, and the pressure is 10-15Mpa.
[0035] Compared with the prior art, the present invention has the following beneficial effects: the modified aluminosilicate prepared by the hydrothermal method can adjust the size and shape as needed, has an extremely high specific surface area and a interconnected network microporous structure, can effectively fix the loaded silver ions, and slowly release the silver ions to achieve the purpose of long-term effective antibacterial, and solves the problem of silver ion discoloration; compared with common gas reduction, high-temperature reflux and other processes, the preparation of the modified silver-loaded aluminosilicate by the present invention is simpler to operate and has a higher loading rate; the antibacterial ABS composite material prepared by the present invention has good antibacterial agent particle dispersion effect, good antibacterial effect, long effective time, and excellent mechanical properties. DETAILED DESCRIPTION
[0036] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0037] Embodiment 1:
[0038] S1: 50g of nano oxide with an average pore size of 25nm and 10g of microporous alumina with an average pore size of 250nm are uniformly mixed at 200rpm to obtain a mixture, and then 1% of the mass of the mixture is added with a titanate coupling agent and mixed at a high speed of 500rpm for 6min, ultrasonicated at room temperature for 30min, and allowed to stand for 24h. Then, a hydrothermal method is used to control the hydrothermal temperature to 150°C and the hydrothermal time to 10h, and the pH is adjusted to 4. After drying, porous aluminosilicate is obtained.
[0039] The aluminum-silicon ratio of the porous aluminosilicate is 1:15.
[0040] The nano-oxides include 35g of nano-zinc oxide, 5g of nano-silicon oxide, and 10g of nano-titanium oxide, and the ultrasonic treatment conditions are 60Hz, 1000W.
[0041] S2. Prepare the following raw materials: 3 g of tetraethyl orthosilicate, 42 g of anhydrous ethanol, 1.0 g of porous aluminosilicate, 0.8 g of silver nitrate, and 40 g of ethylene glycol.
[0042] S3, adding ethyl orthosilicate to anhydrous ethanol, and then adding porous aluminosilicate to carry out heating reaction at 140° C. for 35 hours to obtain modified aluminosilicate;
[0043] S4. In a light-proof environment, dissolve silver nitrate in ethylene glycol and adjust the pH to 2-3, stir for 3-5 minutes, then add modified aluminosilicate and heat at 85-95°C for 48-72 hours, then wash with deionized water and dry at 50-70°C for 4 hours, and finally vacuum dry at 80-100°C for 2 days to obtain modified silver-loaded aluminosilicate.
[0044] S5. Prepare the following raw materials according to the mass proportions: 100 parts of ABS recycled broken pieces, 0.5 parts of modified silver-loaded aluminosilicate, 0.5 parts of polyethylene wax dispersant, 0.5 parts of stearic acid lubricant, and 0.5 parts of antioxidant 225;
[0045] S6. Evenly mix the ABS recycled material with modified silver-loaded aluminosilicate, polyethylene wax dispersant, stearic acid lubricant and antioxidant, and finally extrude and granulate in a twin-screw extruder to obtain antibacterial masterbatch. The temperature of the first zone of the twin-screw extruder is 190°C, the second zone is 195°C, the third zone is 215°C, the fourth zone is 220°C; the fifth zone is 220°C, the residence time is 2 minutes, and the pressure is 12Mpa;
[0046] S7. Press the antibacterial masterbatch into sheets on a flat-plate vulcanizer injection molding machine to obtain standard test pieces with a thickness of 4 mm for testing antibacterial composite plastic materials.
[0047] Embodiment 2:
[0048] The only difference from Example 1 is that the aluminum-silicon ratio of the porous aluminosilicate in step S1 is 1:25.
[0049] Embodiment 3:
[0050] The only difference from Example 1 is that the mass fraction of the modified silver-carrying aluminosilicate in step S5 is 3.
[0051] Embodiment 4:
[0052] The only difference from Example 1 is that the mass fraction of the polyethylene wax dispersant in step S5 is 1.5.
[0053] Embodiment 5:
[0054] The only difference from Example 1 is that the mass fraction of the stearic acid lubricant in step S5 is 1.5.
[0055] Embodiment 6:
[0056] The only difference from Example 1 is that the mass of ethylene glycol in step S2 is 70 g.
[0057] Embodiment 7:
[0058] The only difference from Example 1 is that the mass of silver nitrate in step S2 is 1.6 g.
[0059] Comparative Example 1:
[0060] The only difference from Example 1 is that no modified silver-carrying aluminosilicate is added.
[0061] Comparative Example 2:
[0062] The only difference from Example 1 is that the amount of modified silver-carrying aluminosilicate added is 0.1 part.
[0063] Antibacterial test of composite materials: GB / T 31402 is used for antibacterial experiments, and the test items are Escherichia coli and Staphylococcus aureus. The antibacterial specimen is 40mm×40mm×4mm. The specimen is rinsed with distilled water and irradiated with ultraviolet light for use. Add bacterial suspension to each negative and control antibacterial specimen, cover with disinfected PE film, and culture in a 37℃ constant temperature box for 15 days. Count the number of colonies. Repeat the test 3 times and take the average value of the results. The average value will be used to calculate the antibacterial rate. The calculation formula for the antibacterial rate is:
[0064] R(%)=(AB) / A×100%
[0065] Wherein, R is the antibacterial rate, %; A is the average number of residual bacteria recovered in the negative control group, cfu / piece; B is the average number of residual bacteria recovered in each group of samples of the nano-silver-loaded resin base, cfu / piece.
[0066] The effective antibacterial time of the antibacterial material is long, and the verification cycle using conventional experiments is too long. The inorganic antibacterial agent contained in the antibacterial material will release metals and their ions. These antibacterial components with bactericidal function will directly contact and enter the cells to kill microorganisms, or become active centers to release hydroxyl radicals and active oxygen ions to kill bacteria. Therefore, the present invention uses the example samples and comparative example samples to culture with the bacterial solution at a constant temperature under a shaking state, observes the turbidity of the bacterial solution at different times, and indicates the antibacterial durability of the material based on the transmittance. The higher the transmittance, the better the antibacterial effect.
[0067] Table 1: Test results of antibacterial composite plastic materials prepared in Examples 1-8 and Comparative Examples 1-2
[0068]
[0069]
[0070] In summary, the modified aluminosilicate prepared by the hydrothermal method of the present invention can adjust the size and shape as needed, has an extremely high specific surface area and a interconnected network microporous structure, can effectively fix the loaded silver ions, and slowly release the silver ions to achieve the purpose of long-term effective antibacterial, and solves the problem of discoloration of silver ions; compared with common gas reduction, high-temperature reflux and other processes, the preparation of the modified silver-loaded aluminosilicate by the present invention is simpler to operate and has a higher loading rate; the antibacterial ABS composite material prepared by the present invention has good antibacterial agent particle dispersion effect, good antibacterial effect, long effective time, and excellent mechanical properties.
[0071] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0072] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0073] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. An antibacterial ABS composite material, characterized in that: The composite material is prepared from the following raw materials in parts by weight: 100 parts of ABS recycled and crushed flakes, 0.5 parts of modified silver-loaded aluminosilicate, 0.5 parts of polyethylene wax dispersant, 0.5 parts of stearic acid lubricant, and 0.5 parts of antioxidant 225; The modified silver-loaded aluminosilicate includes the following raw materials in parts by weight: 3 parts of ethyl orthosilicate, 42 parts of anhydrous ethanol, 1.0 parts of porous aluminosilicate, 1.6 parts of silver nitrate, and 40 parts of ethylene glycol; The porous aluminosilicate has a size of 50-150nm, with an aluminum-silicon ratio of 1:15; The preparation method of modified silver-carrying aluminosilicate comprises the following steps: S1, adding ethyl orthosilicate to anhydrous ethanol, then adding porous aluminosilicate and mixing evenly, and then heating to react to obtain modified aluminosilicate; S2, in a light-proof environment, dissolving silver nitrate in ethylene glycol and stirring, then adding modified aluminosilicate and heating, and finally washing and drying to obtain modified silver-loaded aluminosilicate; Step S1: the heating reaction temperature is 140°C and the time is 35h; Step S2: the heating temperature is 85-95°C and the time is 48-72h; Step S2 drying is vacuum drying at a temperature of 80-100° C. for 2 days; The modified silver-loaded aluminosilicate is in a ribbon-like stacking morphology with a size of 50-150 nm; The preparation method of the antibacterial ABS composite material comprises the following steps: uniformly mixing ABS regenerated and crushed flakes with modified silver-loaded aluminosilicate, polyethylene wax dispersant, stearic acid lubricant, and antioxidant, and finally extruding and granulating in a twin-screw extruder; The temperature of the twin-screw extruder zone 1 is 190°C, zone 2 is 195°C, zone 3 is 215°C, zone 4 is 220°C, zone 5 is 220°C, the residence time is 2 min, and the pressure is 12 MPa.
Citation Information
Patent Citations
Antibacterial ABS modified plastic
CN104987648A
Antibacterial ABS resin
CN105670202A
Antibacterial master batch and preparation method thereof, and antibacterial ABS resin
CN113072780A
Method for preparing novel antibacterial electronic cigarette appearance material
CN105038090A
Modified zeolite of nano silicon dioxide mesoporous covering structure and preparation and application of modified zeolite
CN108033456A